THE ANALYZED WASTE MANAGEMENT KAYUJATI MARKET IN TEMBILAHAN INDRAGIRI HILIR REGENCY IN 2018. - Christine Vita Purba; Alhidayati Alhidayati; Leon Candra; Sartika Sartika (JURNAL KESMAS DAN GIZI (JKG), 2019)
ABSTRACT Based on data from the Office of the Environment and cleanliness of Indragiri Hilir Regency, the amount of midden per day were approximately 57.312 tons, amount of middens per week were 401.18 tons and per month were 1719.36 ton. Kayujati market resulting waste in every day about 6000 kg/day. The research purpose was to analyzed waste management Kayujati market in Tembilahan Indragiri Hilir Regency in 2018. This research was qualitative descriptive, that was conducting observation and depth interviews. Informant in this research was 6 persons. Variables was researched among other was waste sorting, collecting and storage in source location, transportation. The results showed that there was no separation between organic and inorganic waste, waste collection was carried out by the market administrator who was conducted once a day, during the day with a fee is two thousand rupiah per kiosk, garbage transportation was carried out by janitors using brooms and scopes, even by hand, and then, it is conducted three times in a day in the morning, afternoon and evening. And total 5 person per work shift. Suggestions for market administrator to require traders to own their own trash, sorting between organic and inorganic waste so that they fulfill health requirements, and sanction the traders who dispose of their trash not in place. Keywords : Waste Management, Market